Analyzing primary resonant dynamics of functionally graded nanoplates based on a surface third-order shear deformation model. (October 2018) - Gholami, Y.; Ansari, R.; Gholami, R.; Rouhi, H.
Abstract: In the context of Gurtin-Murdoch (GM) surface elasticity theory, a size-dependent third-order shear deformable plate model is developed herein in order to study the nonlinear forced vibration behavior of rectangular nanoplates with considering surface stress effect. Nanoplates are assumed to be made of functionally graded materials (FGMs) whose properties are graded in the thickness direction based on a power-law distribution. First, the constitutive relations of GM model are matricized. Then, Hamilton's principle is used to derive the governing equations. The variational differential quadrature, a numerical Galerkin, time periodic discretization, and pseudo arc-length methods are also employed for numerical solution of the geometrically nonlinear forced vibration problem. The frequency-response curves of rectangular nanoplates with different boundary conditions are investigated for different values of thickness, power-law index, surface constants and side length-to-thickness ratio. The results reveal that the surface stress has an important influence on the frequency-response curve of nanoplates at very small scales. Highlights: Nonlinear forced vibrations of thin nanoplates including surface effects are investigated. Third-order shear deformation theory is used. A novel numerical solution approach is proposed based the VDQ method. Influences of thickness, surface parameters and boundary conditions on the frequency–amplitude curves are studied.